(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The primary aim of this investigation is to uncover and discover the fundamental factors that impact on the use of wealth management services amongst investors in Delhi (National Capital Region) because to the best of researchers’ knowledge there is no available information on the present study. Research on investment behavior has indicated that purpose to employ in an exacting behavior is a role of the individual’s attitudes headed for that action and those characters are reliable with performance (Ajzen, 2019; Ajzen & Fishbein, 2018; 2020). Therefore, the attitudinal element was deemed significant in this investigation and variables connected optimistically or pessimistically to the attitudes were taken predictors of the possibility of proper use of wealth management services. The current research is carried out to evaluate the influence of financial literacy, risk appetite, personal beliefs, subjective norms and attitude on investor’s investment behavior.